Pengembangan Media Pembelajaran Menggunakan Pop Up Book Digital pada Pembelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Ramadhani, Yola; Rahmatina, Rahmatina (Lembaga Yasin AlSys, 2025)
The lack of digital learning media aligned with current technological developments and the limited variety of media used in instructional processes serve as the background for this study. The aim of this research is to develop a Pop Up Book Digital learning medium that is valid, practical, and effective for use in Pancasila Education for fifth-grade elementary school students. This is a research and development (R&D) study employing the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through validation questionnaires involving subject matter experts, language experts, and media experts, as well as practicality questionnaires from teachers and students. The trial was conducted with 19 fifth-grade students from SDN 02 Tanjung Barulak and 22 fifth-grade students from SDN 13 Tanjung Barulak as the primary subjects. Data analysis techniques used a Likert scale to measure validity, practicality, and effectiveness. The results show that content validity reached 82.5%, language validity 87.5%, and media validity 95%, all of which fall into the